Social-ecological-technological systems consequences of mining: An analytical framework for more holistic impact assessments. Issue 4 (December 2021) - Nilsson, Annika E.; Avango, Dag; Rosqvist, Gunhild
Highlights: Assessing sustainability impacts of mining requires new, holistic approaches. Impact assessments must consider social-ecological-technological systems dynamics. Effects of climate change and regimes shifts need attention in impact assessment. Abstract: Understanding the impacts of extractive industries on sustainable development requires analyzing them as part of dynamic social-ecological-technological systems. Building on insights from studies of social-ecological systems and socio-technical systems, as well as fieldwork on the impacts of mining in the Nordic Arctic, this article presents an analytical framework for co-production of knowledge about the role of industrial or infrastructure projects for regional development. We use this framework to analyze Swedish mining policy, assessment guidelines, and environmental impact assessments for three mining projects in Arctic Sweden. We conclude that Swedish mining policy and guidelines for impact assessments neglect key aspects of social-ecological-technological systems, including the impacts of climate change, and treat many social aspects of sustainable development in a cursory manner. We suggest that more systematic analysis of the dynamics of social-ecological-technological systems would facilitate more transparent decision making and help identify the potential role of proposed mining projects in pathways towards sustainable development in northern regions.